Syntax-phonology mapping and the Tongan DP. Issue 1 (1st April 2016) - Ahn, Byron
Tongan, a Polynesian language, is almost entirely head-initial. There are some exceptions to this, including Demonstrative enclitics and the so-called Definitive Accent (Churchward 1953 ), which appears to be a stress-shift operation, typically in the rightmost word of the DP.* One question that arises here is: where does the morphophonological status of being an enclitic come from – particularly in a rather radically head-initial language? By investigating the distributional properties of the Definitive Accent, it will become clear that this is the result of syntactic and phonological structures proceeding without any direct appeal to morphophonological properties. A new formal analysis presented here derives the positions of the Definitive Accent and possible prosodic phrasings, appealing to independently motivated phonological constraints applying to structures with three cross-linguistically supported movement operations. It is shown that achieving this requires neither including morpheme-indexed constraints, nor having lexemes pre-specified with morphophonological properties such as "enclitic" or "prefix". Finally, Tongan Definitive Accents raise important issues about the immutability of phases. Specifically, it must be that Phonology may access and manipulate previously spelled out material in a way that Syntax cannot, which is in fact exactly what a Minimalist architecture predicts.